Technical Note: A deuterated 13C‐urea reference for clinical multiparametric MRI prostate cancer studies including hyperpolarized pyruvate. Issue 7 (11th May 2020) - Harlan, Collin J.; Xu, Zhan; Michel, Keith A.; Walker, Christopher M.; Lokugama, Sanjaya D.; Martinez, Gary V.; Pagel, Mark D.; Bankson, James A.
Abstract : Purpose: Metabolic magnetic resonance imaging (MRI) using hyperpolarized [1‐ 13 C]‐pyruvate offers unprecedented new insight into disease and response to therapy. 13 C‐enriched reference standards are required to enable fast and accurate calibration for 13 C studies, but care must be taken to ensure that the reference is compatible with both 13 C and 1 H acquisitions. The goal of this study was to optimize the composition of a 13 C‐urea reference for a dual‐tuned 13 C/ 1 H endorectal coil and minimize imaging artifacts in metabolic and multiparametric MRI studies involving hyperpolarized [1‐ 13 C]‐pyruvate. Methods: Due to a high amount of Gd doping for the purpose of reducing the spin‐lattice relaxation time (T1 ) of urea, the 1 H signal produced by a reference of 13 C‐urea in normal water was rapidly relaxed, resulting in severe artifacts in heavily T1 ‐weighted images. Hyperintense ringing artifacts in 1 H images were mitigated by reducing the 1 H concentration in a 13 C‐urea reference via deuteration and lyophilization. Several references were fabricated and their SNR was compared using 1 H and 13 C imaging sequences on a 3T MRI scanner. Finally, 1 H prostate phantom imaging was conducted to compare image quality and 1 H signal intensity of normal and deuterated urea references. Results: The deuterated 13 C‐urea reference provides strong 13 C signal for calibration and an attenuated 1 H signal that does not interfere with heavily T1 ‐weighted scans. Deuteration and lyophilization were fundamental to the reduction in 1 H signal and hyperintense ringing artifacts. There was a 25‐fold reduction in signal intensity when comparing the nondeuterated reference to the deuterated reference, while the 13 C signal was unaffected. Conclusion: A deuterated reference reduced hyperintense ringing artifacts in 1 H images by reducing the 1 H signal produced from the 13 C‐urea in the reference. The deuterated reference can be used to improve anatomical image quality in future clinical 1 H and hyperpolarized [1‐ 13 C]‐pyruvate MRI prostate imaging studies.